Multi-channel based on power control protocol for mobile ad hoc networks - LI Dong-sheng; XIANG Yong; SHI Mei-lin (Tongxin xuebao)
To solve the collision problem brought by power control in mobile ad-hoc network（MANET）,multi-channel MAC protocol and on-demand minimum energy routing protocol were employed,to carry out a multi-channel based power control ad hoc network,MCBPC.This architecture controlled the frequent changes of topology,decreased the probability of contact brought by power control,and achieved the goal of energy conservation.Simulation results indicate that compared with AODV@IEEE 802.11 approaches,the proposed MCBPC solution achieves about 90% increase in the throughput and network lifetime,and 30% increase in the packet delivery ratio.